2021
DOI: 10.3390/plants10020322
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Characterization of Lectin Receptor Kinases in Saccharum spontaneum L. and Their Responses to Stagonospora tainanensis Infection

Abstract: Sugarcane is an important sugar and bioenergy ethanol crop, and the hyperploidy has led to stagnant progress in sugarcane genome decipherment, which also hindered the genome-wide analyses of versatile lectin receptor kinases (LecRKs). The published genome of Saccharum spontaneum, one of the two sugarcane ancestor species, enables us to study the characterization of LecRKs and their responses to sugarcane leaf blight (SLB) triggered by Stagonospora tainanensis. A total of 429 allelic and non-allelic LecRKs, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Previous studies identified 225, 234 and 467 LRR-RLK genes in soybean [11], tomato [13] and Arabidopsis [14], respectively. Sugarcane is subjected to various abiotic and biotic stresses during growth and development [54,58]. It is worth noting that the members of LRR-RLK genes in all of these species mentioned are larger than those in Arabidopsis, which might be due to their small genome.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies identified 225, 234 and 467 LRR-RLK genes in soybean [11], tomato [13] and Arabidopsis [14], respectively. Sugarcane is subjected to various abiotic and biotic stresses during growth and development [54,58]. It is worth noting that the members of LRR-RLK genes in all of these species mentioned are larger than those in Arabidopsis, which might be due to their small genome.…”
Section: Discussionmentioning
confidence: 99%
“…The field was watched throughout the plant life cycle, especially after appearance of sugarcane leaf blight disease (SLB) symptoms, and five different disease development stages were defined according to the previous report [54]. The leaf samples that had no visible sign of the SLB symptom and without pathogenic spores or hyphae observed under the microscope were represented as control [54]; Supplementary Material S5 shows the details. Three biological replicates were performed for each infection stage and for control (healthy), and a total of 18 samples were obtained.…”
Section: Plant Materials Rna Extraction and Qrt-pcr Analysismentioning
confidence: 99%
See 3 more Smart Citations